'A long way from earning': (re)producing violence at the nexus of shame and blame. (2nd January 2021) - Nussey, Charlotte
ABSTRACT: Symbolic violence is (re)produced within families at the nexus of blame and shame. This paper presents an understanding of symbolic violence that extends beyond processes of internalisation, in which shame is directed against the self, to questions of processes of reproduction within families, in which shame is externalised through blame. Drawing on mother-tongue life-history interviews with mothers and grandmothers in rural KwaZulu-Natal, the paper explores how this nexus of blame and shame is situated at the intersect of race and gender. It is bound by intergenerational poverty and educational exclusion that span the apartheid and post-apartheid eras in South Africa. Our understandings of gendered poverty thus need to attend to these intergenerational processes of shaming, in which pervasive neoliberal discourses around individual effort and success mask structural constraints, potentially damaging relationships within families and across social networks.